Farrerol Alleviates Myocardial Ischemia/Reperfusion Injury by Targeting Macrophages and NLRP3 - Zhou, Lin; Yang, Shuhui; Zou, Xiaoming (Frontiers in Pharmacology, 2022)
Myocardial ischemia/reperfusion (I/R) injury is associated with high mortality and morbidity, however, it has no curative treatment. Farrerol (FA), an active compound extracted from rhododendron, has antibacterial, anti-inflammatory, and antioxidant activities, but its effect and mechanism of FA in I/R injury remain unclear. Here, we found that FA alleviated myocardial I/R in vivo, and decreased the secretion of myocardial injury factors (CK-MB, LDH, troponin-1, and NT-proBNP) while inhibiting the release of inflammatory factors (IL-1β, IL-6, and TNF-α). FA could also alleviate excessive oxidative stress by elevating the level of antioxidant enzymes and reducing oxidation products; and decreased reduced the expression of apoptosis-associated proteins (cleaved caspase-3, Bax, and Bcl-2). However, inhibiting the autophagic pathway or knocking out the Nrf2 gene did not eliminate the myocardial protective effect of FA, but interestingly, macrophage clearance and Nlrp3 deficiency effectively blocked the myocardial protective effect of FA. In addition, FA suppressed NLRP3 inflammasome activation by interfering with NLRP3 and NEK7. In conclusion, these results support drug-targeted macrophage therapy for myocardial I/R and indicate that FA may be used as an immunomodulator in clinical therapy for myocardial I/R.